SHOWROOM MOBIL HONDA DENGAN PENERAPAN ARSITEKTUR KONTEMPORER DI KOTA KUALA KAPUAS - Viki Ramadhan; Nurfansyah Nurfansyah; Yuswinda Febrita (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
The Honda car showroom with the application of contemporary architecture in Kuala Kapuas is a showroom building design that focuses on visual and functional aspects that aim to show the image of Honda products to consumers and meet the needs of car transportation sales facilities in Kuala Kapuas City, especially the Honda brand. This design was motivated by the lack of car transportation sales facilities in Kuala Kapuas and the tips of PT. Honda Trio Raya to continue to provide the best effort in reaching consumers, especially in the Kuala Kapuas area of Central Kalimantan. Contemporary architectural style itself is considered as an architectural style that reflects a quality and novelty, so the concept used to solve this design problem is to apply contemporary architectural principles into the design of the showroom according to the functions and needs of the Honda car showroom itself.